The Effect of Child Sexual Abuse Prevention Song Among Elementary School Children:Pilot Study - Solehati, Tetti; Hermayanti, Yanti; Kosasih, Cecep Eli; Mediani, Henny Suzana (Universitas Aisyah Pringsewu, 2021)
Child Sexual Abuse (CSA) becomes a problem in the world that is quite large and has adverse effects, both short and long term. The prevalence continues to increase every year. Generally, elementary school-age likes to sing a song. Meanwhile, school-age is the time to study. A song is expected to increase knowledge of skills in preventing sexual violence. The objective of this study to assess the effect of education through songs on the level of skill knowledge about preventing CSA in school-age children. The type of research was quasi-experiment with one group pre and post-test design. The sample size used a total sampling that all students became the sample. The study involved 323 students in grades 4-6 at SDN Dayeuhkolot, Bandung Regency. The treatment was an education on prevention of the CSA on school-age children, it was given using the jargon